Integrated Formal Methods : 15th International Conference, IFM 2019, Bergen, Norway, December 2–6, 2019, Proceedings /: 15th International Conference, IFM 2019, Bergen, Norway, December 2–6, 2019, Proceedings. (2020) - Unknown
No abstract available